(untitled) (International Journal of Statistical Sciences, 2024)
This paper aimed to assess the technical efficiency (TE) of aman rice farms and analyzed the major factors affecting inefficiency of aman rice farms. In doing so, a multistage random sampling method was used to collect primary data from a survey of 455 rice farmers between May and June in 2023 in Kaligonj sub-district of Satkhira district. Stochastic frontier approach (SFA) was employed to predict the efficiency of aman rice farms while the Tobit model was used to identify the factors that influence technical inefficiency. The findings of TE ranged from 0.98 to 0.51 with an average score of 0.8469. Technical inefficiency is largely affected by years of schooling, household size, salinity of land, agriculture policy and access to credit variables. The policy implications of this finding is that the government might provide the agricultural extension network so that the extension agent can better engage with targeted farmers rather than just recommendations. International Journal of Statistical Sciences, Vol. 24(2), November, 2024, pp 97-108